Examining the relationship between top management support, product strategies and internal support in new product development success on manufacturing firm in Malaysia - Naimah, Amlus (2013)
New Product Development (NPD) has become a major concern in all types of companies particularly in the manufacturing companies and its success is undeniably vital to the viability, growth and prosperity especially in today’s modern corporation. This research aimed to identify the relationships between the various factors that can generate a stream of market led and technical support for the business operation in Malaysia. The identified factors are top management support, internal and external support, product strategies and training. Through the mail survey, 250 companies have responded to the distributed questionnaires where 37.1 percent respondents were operation managers, 37.1 were marketing manager and 25.8 percent were managers in Malaysia. In this research we use SPSS to analyze the data and test of hypothesis using hierarchical regression with alpha value. However, only 229 or 91.6 percent of the responded questionnaires were usable. The respondents cover 71.2 percent of the manufacturing companies, where 28.8 percent were respondents from the electric and electronic companies. All the companies which responded were involved in product development, with a minimum of one product pattern and a maximum of five product patterns and this covers 59.8 percent of the respondents. The hypotheses used were tested by using correlation and regression techniques. The result of the study supported all the hypotheses. The multiple regression analysis indicated that there are significant relationship among the variables such as top management support, internal/external support, product strategies and training, on the usefulness of the new product development (NPD). It is believed that outcome of this study will benefit the manufacturers, government decision maker in making manufacturing policy, academician in formulating syllabus and the top management of companies into successfully implementing the new product development (NPD) and having the ability to counter any major competitions in future.